Performance and the culture of nationalism tracing rhizomatic lived experiences of South, Central and Southeast Asia - Gooptu, Sarvani; Pandit, Mimasha (Routledge, an imprint of the Taylor & Francis Group, 2023)
This book studies the intersection of performance and nationalism in South Asia.It traces the emergence of the culture of nationalism from the late nineteenth century through to contemporary times. Drawing on various theatrical performance texts, it looks at the ways in which performative narratives have reflected the national narrative and analyses the role performance has played in engendering nationhood. The volume discusses themes such as political martyrdom as performative nationalism, the revitalisation of nationalism through new media, the sanitisation of physical gestures in dance, the performance of nationhood through violence in Tajiki films, as well as K-Pop and the new northeastern identity in India. A unique contribution to the study of nationalism, this book will be useful for scholars and researchers of history, theatre and performance studies, cultural studies, postcolonial studies, modern India, Asian studies, political studies, social anthropology and sociology.